In Vitro Studies of Bacterial Cellulose and Magnetic Nanoparticles Smart Nanocomposites for Efficient Chronic Wounds Healing - Bianca Galateanu; Mihaela-Cristina Bunea; Paul Stanescu; Eugenia Vasile; Angela Casarica; Horia Iovu; Anca Hermenean; Catalin Zaharia; Marieta Costache (Stem Cells International)
The quality of life of patients with chronic wounds can be extremely poor and, therefore, over the past decades, great efforts have been made to develop efficient strategies to improve the healing process and the social impact associated with these conditions. Cell based therapy, as a modern tissue engineering strategy, involves the design of 3D cell-scaffold bioconstructs obtained by preseeding drug loaded scaffolds with undifferentiated cells in order to achieve in situ functional de novo tissue. This paper reports on the development of bionanocomposites based on bacterial cellulose and magnetic nanoparticles (magnetite) for efficient chronic wounds healing. Composites were obtained directly in the cellulose bacterial culture medium by dispersing various amounts of magnetite nanoparticles during the biosynthesis process. After purification and drying, the membranes were characterized by Raman spectroscopy and X-ray diffraction to reveal the presence of magnetite within the bacterial cellulose matrix. Morphological investigation was employed through SEM and TEM analyses on bionanocomposites. The biocompatibility of these innovative materials was studied in relation to human adipose derived stem cells in terms of cellular morphology, viability, and proliferation as well as scaffolds cytotoxic potential.